2015
DOI: 10.1016/j.envint.2014.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Perfluoroalkyl substances and thyroid function in older adults

Abstract: Current understanding of the thyroid disruptive properties of perfluoroalkyl substances (PFASs), particularly in aging populations, is limited. The objectives of this study were to (i) assess associations between thyroid function, as measured by serum thyrotropin (thyroid stimulating hormone, TSH), free thyroxine (fT4), total thyroxine (T4), and total triiodothyronine (T3), and serum perfluorooctane sulfonate (PFOS) and perfluorooctanoic acid (PFOA) in an aging population and (ii) determine if other persistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 50 publications
3
40
0
Order By: Relevance
“…The concentrations of the major PFASs in our study were lower than most reported studies of populations in other countries 4 5 7 11 31 32 36 39 , but comparable with levels detected in other cities from China 6 50 and in recent studies of populations from Norway 51 , South Korea 40 , 20–40 years old females from the United States 36 and Denmark 52 . The highly correlated PFASs in maternal serum, especially PFNA, PFDA and PFUnA, indicated that these chemicals might have common sources of exposure in this area.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The concentrations of the major PFASs in our study were lower than most reported studies of populations in other countries 4 5 7 11 31 32 36 39 , but comparable with levels detected in other cities from China 6 50 and in recent studies of populations from Norway 51 , South Korea 40 , 20–40 years old females from the United States 36 and Denmark 52 . The highly correlated PFASs in maternal serum, especially PFNA, PFDA and PFUnA, indicated that these chemicals might have common sources of exposure in this area.…”
Section: Discussionsupporting
confidence: 83%
“…In human studies, associations between PFOA or PFOS and thyroid disease have been found in general population 26 and in highly exposed Mid-Ohio Valley community children, adults and workers 27 28 29 . However, the results of many other population-based researches on individual thyroid hormones disrupting potencies of PFASs were inconsistent 30 31 32 33 34 35 36 . Null associations between PFASs and thyroid hormones have been also reported 37 38 .…”
mentioning
confidence: 99%
“…However, the association is still inconclusive. Blood PFAS concentrations are negatively correlated with thyroid hormone concentrations according to some studies [ 23 , 25 , 26 ], while other studies showed positive correlations [ 27 , 28 ] or no association [ 29 32 ]. These inconsistent results may be due to the concentration-dependent differential effects of PFASs.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologic and toxicologic studies have reported the potential of PFASs, particularly PFOAs and PFOSs, to act as endocrine-disruptors, impairing thyroid function through pathways including competing for thyroid hormone binding proteins, such as transthyretin (Weiss et al 2009;Ballesteros et al 2017). However, studies on human thyroid hormones and PFAS exposures have not been conclusive (Bloom et al 2010;Melzer et al 2010;Ji et al 2012;Webster et al 2014;Shrestha et al 2015;Yang et al 2016). Modest associations between PFOAs and thyroid hormones (negative for T4 and positive for T3) were reported in a study on 506 PFOA production workers (Olsen and Zobel 2007).…”
Section: Introductionmentioning
confidence: 99%